KEPUASAN PETANI TERHADAP PELAYANAN LEMBAGA PEMASARAN SAWIT DI PROVINSI BENGKULU - Fitria Noprililian; Ketut Sukiyono; Lathifah Khairani; Yovita Anggita Dewi (Pusat Publikasi Jurnal Universitas Islam Kalimantan, 2026)
Oil palm is an important commodity that plays a role in increasing farmers’ income, where marketing success is greatly influenced by the quality of service provided by marketing agencies as well as the factors affecting it. Bengkulu Province is one of the regions on the island of Sumatra that is developing the oil palm plantation industry; the objective of this study is to analyze the level of farmer satisfaction with the services provided by oil palm marketing agencies in Bengkulu Province. It also aims to analyze the factors that influence farmers’ satisfaction with the services provided by oil palm marketing agencies in Bengkulu Province. The sample used in this study was selected through purposive sampling, specifically farmers who actively sell their harvest to marketing agencies. Data analysis was conducted using the Customer Satisfaction Index (CSI) and Multinomial Logistic Regression methods. Farmer satisfaction is influenced by service qualitywhich encompasses tangible aspects, reliability, responsiveness, assurance, and empathy as well as farmer characteristics such as age, education level, land area, selling price, distance to the marketing agency, and duration of collaboration. The results of the study indicate that farmers are satisfied with the services provided by palm oil marketing agencies in Bengkulu Province. This level of satisfaction is influenced by factors such as age and the duration of the farmer’s collaboration with the marketing agency. Thus, farmer characteristics play a role in shaping the level of satisfaction with the services provided by palm oil marketing agencies in Bengkulu Province.